Reliability Analysis of ZZ Distribution Under Zero Failure Data - LEI Lu; ZHANG Guozhi; WANG Ping (Journal of Harbin University of Science and Technology)
It is a deviation reality that lifespan of some products is described by common distributions. However，the ZZ distribution can better describe the lifespan distribution of this type of product. In order tostudy the reliability of the ZZ distribution under the condition of no failure data, and the reliability function is transformed, and the concavity and convexity is used to obtain a more precise relationship between the reliability of the products at each detection time Further, under the prior distribution is the uniform distribution or more general distribution, Bayesian Estimation of the reliability at each moment is given Meanwhile, according to the optimal confidence lower limit formula of known function with confidence level of 1－α in the case of no failure data, the optimal confidence lower limit expression of the reliability function is given, and the simplified form that is convenient to use is obtained in several special cases.